2019
DOI: 10.3389/fneur.2019.00405
|View full text |Cite
|
Sign up to set email alerts
|

World-Wide Efficacy of Bone Marrow Derived Mesenchymal Stromal Cells in Preclinical Ischemic Stroke Models: Systematic Review and Meta-Analysis

Abstract: Background: Following extensive, positive results in pre-clinical experiments, Bone Marrow Derived-Mesenchymal Stromal Cells (BM-MSCs) are now being tested as a novel therapy for ischemic stroke in ongoing clinical trials. However, multiple critical questions relating to their translational application remain to be clarified. We performed a comprehensive, systematic review and meta-analysis of pre-clinical studies to evaluate the efficacy of BM-MSCs on functional outcomes after ischemic stroke, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 34 publications
(36 reference statements)
2
42
0
Order By: Relevance
“…There is a substantial body of evidence showing that mesenchymal stem cells (MSCs) improve functional outcomes in rodent models of cerebral ischaemia, as previously reviewed by Satani and colleagues [3]. In phase I/II clinical trials, MSCs have been suggested to be a safe and feasible therapy for ischaemic stroke [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial body of evidence showing that mesenchymal stem cells (MSCs) improve functional outcomes in rodent models of cerebral ischaemia, as previously reviewed by Satani and colleagues [3]. In phase I/II clinical trials, MSCs have been suggested to be a safe and feasible therapy for ischaemic stroke [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…One promising candidate for stroke therapy is mesenchymal stem cells (MSC). A recent systematic review and meta-analysis of 141 studies demonstrated that bone marrow-derived MSC transplantation leads to improvements in functional outcomes in preclinical models of cerebral ischaemia 4. Initially it was thought that MSCs promote repair and ameliorate functional deficits by differentiating into parenchymal cells 5.…”
Section: Introductionmentioning
confidence: 99%
“…103 BM-MSCs administration between 2 and 7 days of injury significantly increased health benefits compared to 12 to 24 hours and >7 days. 119 Delivery at 7 days post-stroke has been most commonly reported in the literature, which may be related to the specific brain environment at that time, with decreased glutamate and brain edema. 120 After stroke, the brain microenvironment is constantly changing, with increased excitotoxicity, inflammatory reaction, and trophic factor expressions.…”
Section: Optimal Dose Timing and Age Of Stem Cellsmentioning
confidence: 99%